Data underpinning the paper: Intra-species variability in Fusarium langsethiae strains in growth and T-2/HT-2 mycotoxin production in response to climate change abiotic factors. - Verheecke-Vaessen, Carol; Lopez-Pietro, Alejandro; García-Cela, Esther; Medina, Angel; Magan, Naresh (Cranfield University, 2021)
The objective of this study was to evaluate the potential intra-species variability of 3 Fusarium langsethiae strains in response to extreme climate change (CC) conditions on an oat-based matrix. The impact of elevated temperature (25 vs 30-34 °C) coupled with increasing drought stress (0.98 vs 0.95 aw ) and elevated CO2 (400 vs 1000 ppm) were examined on lag phases prior to growth, growth rate, and production of the mycotoxins T-2 and HT-2 and their ratio. In comparison to the control conditions (25 °C; 0.98; 400 ppm), exposure to increased temperature (30- 34 °C), showed similar reductions in the lag phase and fungal growth rates of all 3 strains. However, with elevated CO2 a reduction in both lag phases prior to growth and growth rate occurred regardless of the aw examined. For T-2 and HT-2 mycotoxin production, T-2 showed the most intra-species variability in response to the interacting abiotic stress factors, with the 3 strains having different environmental conditions for triggering increases in T-2 production: Strain 1 produced higher T-2 toxin at 25 °C, while Strain 2 and the type strain (Fl201059) produced most at 0.98 aw /30 °C. Only Strain 2 showed a reduction in toxin production when exposed to elevated CO2 . HT-2 production was higher at 25 °C for the type strain and higher at 30-34 °C for the other two strains, regardless of the aw or CO2 level examined. The HT-2/T-2 ratio showed no significant differences due to the imposed interacting CC abiotic conditions.
Keywords: Environmental stress factors'; 'type A trichothecenes'; 'Fusarium'; 'mycotoxigenic fungi'; 'pre-harvest'; 'Food Packaging; Preservation and Safety'